PERSISTENSI RESIDU INSEKTISIDA NABATI PIRETRUM (Chrysanthemum cinerariaefolium) DAN MIMBA (Azadirachta indica) PADA TANAMAN PADI - Agus Kardinan; Tri Eko Wahyono; Nurbetti Tarigan (Pusat Penelitian dan Pengembangan Perkebunan, 2017)
Brown planthopper is still a major problem in rice. Control using botanical insecticides is considered less effective, since its persistence in rice plantation is short. Research on the persistence of botanical insecticide residues of pyrethrum and neem in rice has been conducted in green house of Entomology, Indonesian Spices and Medicinal Crops Research Institute, Bogor from January to December 2016. The research was aimed to determine the persistence of botanical insecticide residue on rice by testing it to brown planthopper mortality. The study was arranged in complete randomized design with six treatments and four replications. The treatment consisted of two pyrethrum formulas (EC); two neem formulas (EC); positive controls of synthetic insecticides (a.i. carbosulfan) and negative control (water). The method used was Leaf Residue Method, by spraying the formula into one month-old rice plants, then 10 brown planthopper nymphs of forth instar were introduced into each plant in the first, second, third and fourth day after spraying. The planthopper mortality was observed in the first, third, sixth, 24th and 48th hours after introduction. The residuals of all insecticides tested were still affecting the mortality of brown planthopper until the fourth day after spraying, although the effectiveness decreased by the time. The average mortality on the first day introduction after spraying ranged between 53-73 % and in the fourth day after spraying was 18-25 %.